Elmer And The Lost Teddy - McKee, David (Andersen Press Ltd, 2008)
One night Elmer hears the sound of crying. It is Baby Elephant who can't sleep because he has lost his teddy. Elmer offers to lend Baby Elephant his teddy for the night and to search for the lost teddy the next day. But Baby Elephant's stays missing until Elmer's cousin Wilbur gets involved in the search. Wilbur plays a joke on Elmer as usual but one that helps Elmer find Baby Elephant's teddy bear. And just in time for bed! From the Hardcover edition.
Keywords: Animals; Elephants; Juvenile Fiction